The Effect of Silicate Modulus on the Properties of Polypropylene Fiber-reinforced Geopolymer Composite Material - Görhan, Gökhan; Danishyar, Fazlullah (Periodica Polytechnica Civil Engineering, 2022)
This study investigated the effect of the silicate moduli on the properties of the geopolymer materials consisting of Class F fly ash (FA) and ground granulated blast furnace slag (GGBFS). For this purpose, geopolymer materials were prepared with alkaline solutions composed of 10 M NaOH and sodium silicate solutions (SSs) with two different silicate moduli (2Ms and 3Ms). The geopolymer mixtures were placed in molds (40 x 40 x 160 mm) and cured at 90 °C for 5 hours. After heat curing, physical, mechanical, XRD, and SEM-EDS analyses were performed on 7-day samples. According to the findings, polypropylene fiber reinforcement improved the flexural and compressive strength of the samples with high GGBFS content. Also, according to SEM-EDS analysis, it was concluded that the higher the CaO content, the lower the compressive strength, and the higher the Al2O3 content, the higher the compressive strength. As a result, the 2Ms SS improved the compressive strength of the samples with higher FA content, while the 3Ms SS improved the compressive strength of the samples with more GGBFS than FA.5% polypropylene fiber-reinforced 3Ms SS samples with 25% FA had the highest compressive strength.